RH3 enhances antiviral defense by facilitating small RNA loading into Argonaute 2 at endoplasmic reticulum–chloroplast membrane contact sites - Juan Huang; Juan Du; Yan Liu; Lu Lu; Yanzhuo Xu; Jianfei Shi; Qing Liu; Qi Li; Yang Liu; Yaqiu Chen; Meng Du; Yiming Zhao; et al. (Nature Communications)
Abstract While RNA silencing is crucial for plant resistance against viruses, the cellular connections between RNA silencing and antiviral responses in plants remain poorly understood. In this study, we aim to investigate this relationship by examining the subcellular localization of small RNA loading and viral replication in Arabidopsis. Our findings reveal that Argonaute 2 (AGO2), a key component of RNA silencing, loads small RNAs at the endoplasmic reticulum (ER)–chloroplast membrane contact sites (MCSs). We identify a chloroplast-localized protein, RNA helicase 3 (RH3), which interacts with AGO2 and facilitates the loading of small RNAs into AGO2 at these MCSs. Furthermore, we discover that MCSs serve as replication sites for certain plant viruses. RH3 also promotes the loading of viral-derived small RNAs into AGO2, thereby enhancing plant antiviral resistance. Overall, our study sheds light on the roles of RH3 in RNA silencing and plant antiviral defenses, providing valuable insights into the cytobiological connections between RNA silencing, viral replication, and antiviral immunity.